ANALISIS PASAL 16 AYAT (1) UNDANG-UNDANG NOMOR 2 TAHUN 2014 TERHADAP INDEPENDENSI NOTARIS DALAM PRAKTIK REKANAN BANK - Aria Roby Putra (JOURNAL OF LAW AND NATION, 2026)
This study aims to analyze the provisions of Article 16 paragraph (1) of Law Number 2 of 2014 concerning the Position of Notary, specifically regarding the principle of notary independence when practicing as a bank partner. This article regulates the obligation of notaries to act honestly, independently, impartially, and protect the interests of the parties involved in every deed. However, in practice, the involvement of notaries as bank partners has the potential to create a conflict of interest, considering the existence of a commercial cooperative relationship between the notary and the bank. This study is a literature study with a normative legal research method, using a statute approach. The results of the analysis show that the cooperation between Notaries and Banks is contractual, but has the potential to violate the principle of neutrality because it creates a special relationship with one of the parties facing the notary. Provisions on honorariums and other rights often trigger conflicts of interest that are contrary to Article 16 paragraph (1) letter a of the UUJN and Article 3 paragraph (4) of the Notary Code of Ethics. This condition can risk reducing the status of the deed to a private deed or making it null and void by law, so an evaluation is needed to maintain the integrity and public trust in the notary profession.